INFORMATION AND TELECOMMUNICATION INFRASTRUCTURE OF INFORMATION SOCIETY: FACTORS AND ACHIEVEMENTS OF REALIZATION - Natalya A. Sadovnikova; Elena N. Klochkova (Статистика и экономика, 2016)
Creation of information society in Russia represents the main objective of social and economic development as is a basis for modernization of national economy in general. According to the State program “Information society (2011-2020)” information technologies become the tool of the solution of problems of modernization in all spheres of national economy, regional development and integration into the world economy, improvement of quality of the human capital and standards of life of the population. The main results of this Program are the advancing growth of the Russian market of information technologies in relation to universal level and achievement of technological independence of the Russian Federation in branch [1].